Targeted therapy of human glioblastoma via delivery of a toxin through a peptide directed to cell surface nucleolin. Issue 5 (18th December 2017) - Dhez, Anne‐Chloé; Benedetti, Elisabetta; Antonosante, Andrea; Panella, Gloria; Ranieri, Brigida; Florio, Tiziana M.; Cristiano, Loredana; Angelucci, Francesco; Giansanti, Francesco; Di Leandro, Luana; d'Angelo, Michele; Melone, Marina; et al.
Abstract : Targeted anticancer therapies demand discovery of new cellular targets to be exploited for the delivery of toxic molecules and drugs. In this perspective, in the last few years, nucleolin has been identified as an interesting surface marker to be used for the therapy of glioblastoma. In this study, we investigated whether a synthetic antagonist of cell‐surface nucleolin known as N6L, previously reported to decrease both tumor growth and tumor angiogenesis in several cancer cell lines, including glioblastoma cells, as well as endothelial cells proliferation, could be exploited to deliver a protein toxin (saporin) to glioblastoma cells. The pseudopeptide N6L cross‐linked to saporin‐S6 induced internalization of the toxin inside glioblastoma cancer cells. Our results in vitro demonstrated the effectiveness of this conjugate in inducing cell death, with an ID50 four orders of magnitude lower than that observed for free N6L. Furthermore, the preliminary in vivo study demonstrated efficiency in reducing the tumor mass in an orthotopic mouse model of glioblastoma. Abstract : A covalent complex (S–S linkage) between the pseudo‐peptide N6L and the toxin Saporin (SAP‐N6L) binds nucleolin on the surface of glioblastoma cells and once internalized induces cell death via apoptosis through inhibition of protein synthesis.